2009
DOI: 10.1093/molbev/msp188
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Next-Generation Transcriptome Sequencing for Functional and Evolutionary Genomics

Abstract: Next-generation sequencing has opened the door to genomic analysis of nonmodel organisms. Technologies generating long-sequence reads (200-400 bp) are increasingly used in evolutionary studies of nonmodel organisms, but the short-sequence reads (30-50 bp) that can be produced at lower cost are thought to be of limited utility for de novo sequencing applications. Here, we tested this assumption by short-read sequencing the transcriptomes of the tropical disease vectors Aedes aegypti and Anopheles gambiae, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 63 publications
3
126
1
Order By: Relevance
“…The final dataset used for de novo transcriptome assembly was 38.9% of its original size. The number of contigs in each assembly, spanning k-mers 33 to 89, was inversely related to k-mer size (Table 2), which is consistent with previous observations (17,18,21,28). The optimum k-mer sizes appeared to be 57 and 65, which had the highest values for most metrics typically used to assess assembly quality (e.g., mean and median contig lengths, N50, and N90), maximum contig length the exception.…”
Section: Resultssupporting
confidence: 88%
“…The final dataset used for de novo transcriptome assembly was 38.9% of its original size. The number of contigs in each assembly, spanning k-mers 33 to 89, was inversely related to k-mer size (Table 2), which is consistent with previous observations (17,18,21,28). The optimum k-mer sizes appeared to be 57 and 65, which had the highest values for most metrics typically used to assess assembly quality (e.g., mean and median contig lengths, N50, and N90), maximum contig length the exception.…”
Section: Resultssupporting
confidence: 88%
“…Recently, de novo transcriptome analyses, that is, de novo assembly of short reads from mRNA without genome reference, have emerged. Several studies have reported the transcriptome sequencing of various non-model species using next-generation sequencing technologies (Gibbons et al 2009, Wolf et al 2010. Although many studies are based on the long-read sequence data using 454 pyrosequencing or used a hybrid approach, the de novo assembly of transcriptome employing short reads (Illumina or SOLiD) has also received extensive attention because of its relatively low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Recent methods and experimental advances have made it possible to perform at de novo sequence projects (Li et al 2009). Many previous pioneering works have suggested that nextgeneration sequencing technologies provide a massive amount of useful information for the transcriptome analysis in non-model organisms (Gibbons et al 2009, Wolf et al 2010. As a powerful tool to explore the expression levels of thousands of genes simultaneously in cell or tissue, the microarray technology was discussed and reviewed in livestock species.…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggests that next-generation sequencing methods will continue to serve as powerful facilitators in this endeavor. The recovery of over 5000 high confidence Drosophila and Tribolium orthologs in the adult head transcriptome of P. hirtus by RNA sequencing underlines the promise of nextgeneration sequencing for exploring the genetic organization of nonmodel organisms, by capitalizing on model species' genome sequences as a reference for assembly and annotation (Gibbons et al, 2009;Juan et al, 2010). The sensitivity of this approach is most impressively highlighted by the detection of circadian rhythm gene transcripts.…”
Section: Discussionmentioning
confidence: 99%